Direct Observation of Sub-Binomial Light - Bartley, Tim; Donati, Gaia; Jin, Xian-Min; Datta, Animesh; Barbieri, Marco; Walmsley, Ian A. (Physical Review Letters)

Strategies for enhancing quantum entanglement by local photon subtraction - Bartley, Tim; Crowley, Philip J. D.; Datta, Animesh; Nunn, Joshua; Zhang, Lijian; Walmsley, Ian (Physical Review A)

Requirements for two-source entanglement concentration - Vidrighin, Mihai; Bartley, Tim; Donati, Gaia; Jin, Xian-Min; Barbieri, Marco; Kolthammer, W. Steven; Datta, Animesh; Walmsley, Ian A. (Quantum Measurements and Quantum Metrology)

Evolving fuzzy pattern trees for binary classification on data streams - Shaker, A.; Senge, R.; Hüllermeier, Eyke (Information Sciences)

"Ihr betet an, was ihr nicht kennt" (Jo 4, 22) - Eine neue Sicht auf die Trinität - Krimphove, Dieter

Kommentar: MaComp Mindestanforderungen an die Compliance-Funktion und die weiteren Verhaltens-, Organisations- und Transparenzpflichten nach §§ 31 ff. WpHG für Wertpapierdienstleistungsunternehmen - Krimphove, Dieter; Kruse, Oliver

Europarecht inklusive CD-ROM mit Gesetzen, Urteilen, Hörfassung und interaktiven Falllösungen - Krimphove, Dieter

Visualization and Collaborative Editing of Simulation Models With Heterogeneous Clients: Implemented Into the Simulator D3FACT - Renken, Hendrik; Brandt, Sascha; Eichert, Felix A.; Klaas, Alexander (Volume 2: 32nd Computers and Information in Engineering Conference, Parts A and B)
Today’s simulation software normally has fixed, built-in editing and visualization views adapted to a specific problem domain. Often this monolithic concept prevents collaborative editing altogether. Even with more flexible concepts, editing simulation models with a heterogeneous set of clients is not possible. In this article we describe a flexible concept for collaborative editing of simulation models with heterogeneous clients, such as web-based, desktop and mobile clients. The clients may even show different editing views adapted to the user’s role. The concept we describe in this paper overcomes several problems: First we need to be able to connect and manage a set of heterogeneous clients in the simulation software. The very different user inputs from the connected clients then need to be processed, interpreted and combined to allow editing in a collaborative way for all users. At last we show a prototypical integration of the presented concept into our research platform d3fact.

Use both lanes: Multi-channel beaconing for message dissemination in vehicular networks - Klingler, Florian; Dressler, Falko; Cao, Jiannong; Sommer, Christoph (2013 10th Annual Conference on Wireless On-demand Network Systems and Services (WONS))

Spherical Visibility Sampling - Eikel, Benjamin; Jähn, Claudius; Fischer, Matthias; Meyer auf der Heide, Friedhelm (Computer Graphics Forum)
Many 3D scenes (e.g. generated from CAD data) are composed of a multitude of objects that are nested in each other. A showroom, for instance, may contain multiple cars and every car has a gearbox with many gearwheels located inside. Because the objects occlude each other, only few are visible from outside. We present a new technique, Spherical Visibility Sampling (SVS), for real-time 3D rendering of such -- possibly highly complex -- scenes. SVS exploits the occlusion and annotates hierarchically structured objects with directional visibility information in a preprocessing step. For different directions, the directional visibility encodes which objects of a scene's region are visible from the outside of the regions' enclosing bounding sphere. Since there is no need to store a separate view space subdivision as in most techniques based on preprocessed visibility, a small memory footprint is achieved. Using the directional visibility information for an interactive walkthrough, the potentially visible objects can be retrieved very efficiently without the need for further visibility tests. Our evaluation shows that using SVS allows to preprocess complex 3D scenes fast and to visualize them in real time (e.g. a Power Plant model and five animated Boeing 777 models with billions of triangles). Because SVS does not require hardware support for occlusion culling during rendering, it is even applicable for rendering large scenes on mobile devices.